Second World War and the Collapse of Colonialism: Causes, Outcomes and Impact: द्वितीय विश्व युद्ध और उपनिवेशवाद का पतन: कारण, परिणाम और प्रभाव - Bandhe, Kaushal Prasad (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
The Second World War (1939–1945) was a decisive event in modern history. It not only altered the balance of power in Europe but also reshaped global politics. The war left European colonial powers, especially Britain and France, economically, politically and militarily weakened. At the same time, nationalist movements in Asia and Africa gained new momentum, which opened the way for a decisive struggle against colonial rule. Emerging superpowers like the United States and the Soviet Union promoted the ideas of self-determination and anti-colonialism, giving international support to independence movements. The establishment of the United Nations also lent legitimacy to the process of ending colonialism. The independence of countries such as India, Indonesia, Vietnam and Ghana sparked a wave of decolonization across Asia and Africa. In this way, the Second World War not only helped reorganize the global political map but also played a major role in the decline of colonialism and the rise of modern nation-states. Abstract in Hindi Language: द्वितीय विश्व युद्ध (1939-1945) आधुनिक इतिहास की एक निर्णायक घटना थी जिसने न केवल यूरोप की शक्ति-संतुलन प्रणाली को बदला बल्कि विश्व राजनीति को भी नए सिरे से परिभाषित किया। युद्ध ने यूरोपीय उपनिवेशवादी शक्तियों विशेषकर ब्रिटेन और फ्रांस को आर्थिक, राजनीतिक और सैन्य दृष्टि से अत्यंत कमजोर कर दिया। इसके साथ ही एशिया और अफ्रीका में राष्ट्रवादी आंदोलनों को नई ऊर्जा मिली, जिसने उपनिवेशवाद के विरुद्ध निर्णायक संघर्ष की राह प्रशस्त की। अमेरिका और सोवियत संघ जैसे नए महाशक्तियों ने “आत्मनिर्णय” और “उपनिवेशवाद-विरोध” की विचारधारा को बढ़ावा दिया, जिससे स्वतंत्रता आंदोलनों को अंतरराष्ट्रीय समर्थन प्राप्त हुआ। संयुक्त राष्ट्र संघ की स्थापना ने भी उपनिवेशवाद के अंत की प्रक्रिया को वैधता प्रदान की। भारत, इंडोनेशिया, वियतनाम और घाना जैसे देशों की स्वतंत्रता ने एशिया और अफ्रीका में डिकॉलोनाइजेशन की लहर को जन्म दिया। इस प्रकार द्वितीय विश्व युद्ध न केवल वैश्विक राजनीतिक मानचित्र को पुनः व्यवस्थित करने में सहायक रहा बल्कि उपनिवेशवाद के पतन और आधुनिक राष्ट्र-राज्यों के उदय का प्रमुख कारण भी सिद्ध हुआ। Keywords: द्वितीय विश्व युद्ध, उपनिवेशवाद, स्वतंत्रता आंदोलन, संयुक्त राष्ट्र संघ, भारत, अफ्रीका, एशिया, राष्ट्रवाद, शीत युद्ध।